PLASTINATION OF WHOLE BRAIN SPECIMEN AND BRAIN SLICES - WADOOD, ARBAB ABDUL; JABBAR, ABDUL; DAS, NIRMAL (Journal of Ayub Medical College Abbottabad, 2001)
Background: The human dead body specimens are plastinated for teaching purposes in medical institutions, using silicone. The silicone impregnated whole brain specimens and brain slices do not give satisfactory results. Methods: In the present study the brain specimens were plastinated with another polymer known as Polyester-Copolymer. The brain specimens were first preserved and then fixed with 5% formalin. The specimens were then dehydrated and degreased in a volatile solvent acetone. The specimens were placed in Polyester- Copolymer solution which penetrated the brain tissue both intracellulary and intercelluraly. The specimens were then cured by gas method. Results: The whole brain specimens and brain slices plastinated with Polyester-Copolymer were dry, odorless, handy and durable. It also gives a clear visual contrast between grey and white matter in brain slices whereas the brain specimens plastinated with silicone are flexible and sticky. There was no color contrast between grey and white matter. Conclusion: The polyester impregnated brain specimens and slices are non-toxic and ideal for teaching purposes and examinations. They require minimal aftercare. The whole organ serial sections of plastinated brain specimens will help 3- dimensional study of the normal brain and will improve the assessment of brain pathology.